An Experimental Study on Soil Stabilization by Using Cement and Incinerated Bottom Ash (International Journal of Innovative Research in Computer Science & Technology, 2022)
This main objective of this study is to  improve the strength of peat soil by adding industrial waste  as a filler and cement as a binder. Peat soil are known to  have a weak strength and a very high settlement problem.  However, past researches have shown that the strength of  peat could be improved by using soil stabilization method.  In this study, the peat stabilization project includes using  bottom ash as the industrial waste which acts as a filler, Portland-limestone cement (PLC) as the binder and the  implementation of Bottom Ash as an additive along with the  process control agent (PCA) and without process control  agent (WPCA). The compressive strength (CS) test are  conducted to further study the effect of bottom ash in the  strength of stabilized peat. The physical properties of the  soil are also studied which includes the density, moisture  content, porosity, specific gravity and shrinkage. In order to  compare the results, different variation of samples with  bottom ash & sand along with PLC are also used to  distinguish the roles of different fillers and chemical  additive. The comparison will further indicate whether the  combination of bottom ash and PLC are suitable for the  study of peat stabilization. The proportion for the mix  design will be 5 parts of filler (bottom ash/sand), 3 parts of  PLC, 5 parts of peat. The samples were casted in the 100  * 100* 100 mm moulds and then were opened after 30 days.  The experiments are carried out after the samples have been  air cured for 28 days. The compressive strength of the  stabilized peat with bottom ash and PLC produces the  strength at 3.6 MPa compared to the other samples while as  from the previous researches, Peat with sand & PLC having  a compressive strength of 0.79MPa. The result shows that  the combination of bottom ash as the filler can be used to  further improve the strength of peat stabilization.
Keywords: Bottom Ash; Compressive Strength; Marshy Soil; Strength; Stabilization